2021
DOI: 10.1113/jp281063
|View full text |Cite
|
Sign up to set email alerts
|

Brain blood and cerebrospinal fluid flow dynamics during rhythmic handgrip exercise in young healthy men and women

Abstract: Key points The cerebral fluid response to exercise, including the arterial and venous cerebral blood flow (CBF) and cerebrospinal fluid (CSF), currently remains unknown. We used time‐resolved phase‐contrast magnetic resonance imaging to assess changes in CBF and CSF flow dynamics during moderate‐intensity rhythmic handgrip (RHG) exercise in young healthy men and women. Our data demonstrated that RHG increases the cerebral arterial inflow and venous outflow while decreasing the pulsatile CSF flow during RHG. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…It must be noted, however, that this extrapolation does not account for many physiological factors that may vary during the course of 1 h, 24 h or even decades. In fact, recent studies have observed that exercise [ 28 , 29 ], blood flow and blood pressure [ 6 , 30 , 31 ], as well as sleep [ 17 , 32 ] and respiration [ 33 38 ] contribute to changes in CSF flow. Moreover, overlap of stroke volume measurements between consecutive cycles was not considered in this extrapolation and should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted, however, that this extrapolation does not account for many physiological factors that may vary during the course of 1 h, 24 h or even decades. In fact, recent studies have observed that exercise [ 28 , 29 ], blood flow and blood pressure [ 6 , 30 , 31 ], as well as sleep [ 17 , 32 ] and respiration [ 33 38 ] contribute to changes in CSF flow. Moreover, overlap of stroke volume measurements between consecutive cycles was not considered in this extrapolation and should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that aortic stiffness and transmission of pulsatile flow into the microcirculation may lead to quantifiable changes in brain volume and increased WMH burden. A recent study conducted by Tarumi et al in young adults investigated cardiovascular variables and cerebral blood flow in response to repeated bouts of rhythmic handgrip exercise using phase-contrast MRI ( Tarumi et al, 2021 ). Using a similar relative intensity of handgrip exercise (30-40% MVC), HR, BP, CVRi, cerebral blood flow, and respiratory rate increased during rhythmic handgrip exercise despite no change in vessel cross-sectional area ( Tarumi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Tarumi et al in young adults investigated cardiovascular variables and cerebral blood flow in response to repeated bouts of rhythmic handgrip exercise using phase-contrast MRI ( Tarumi et al, 2021 ). Using a similar relative intensity of handgrip exercise (30-40% MVC), HR, BP, CVRi, cerebral blood flow, and respiratory rate increased during rhythmic handgrip exercise despite no change in vessel cross-sectional area ( Tarumi et al, 2021 ). Thus, higher resistance in the cerebral vessels may attenuate an increase in cerebral blood flow and prevent cerebral hyperperfusion during rhythmic handgrip exercise, which may represent a compensatory myogenic response to a hypertensive stimulus in order to dampen pulsatile flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations